2021
DOI: 10.1093/ejo/cjab010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of force magnitude on the first and second maxillary molars in cervical headgear therapy

Abstract: Summary Aim To study the effect of force magnitude on the maxillary first and second molars in cervical headgear (CHG) therapy. Material and methods In this controlled clinical trial, patients (n = 40) were treated with CHG with a light (L, 300 g, n = 22) or a heavy force (H, 500 g, n = 18) magnitude. The subjects were asked to wear CHG for 10 hours a day for 10 months. The outer bow of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
5
0
2
Order By: Relevance
“…The maxillary molar movement in the distal direction is not all bodily movement, but tilting can also occur during HG therapy ( 23 , 28 , 29 , 50 ). In our previous study, maxillary first and second molars were found have tipped more distally with heavy force than with light force ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maxillary molar movement in the distal direction is not all bodily movement, but tilting can also occur during HG therapy ( 23 , 28 , 29 , 50 ). In our previous study, maxillary first and second molars were found have tipped more distally with heavy force than with light force ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…The maxillary molar movement in the distal direction is not all bodily movement, but tilting can also occur during HG therapy ( 23 , 28 , 29 , 50 ). In our previous study, maxillary first and second molars were found have tipped more distally with heavy force than with light force ( 50 ). The follow-up period in this study was rather short, 10 months, and thus not all patients had early permanent dentition by the end of the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Talvitie et al . 21 mencionan que la aplicación de fuerzas moderada (500 g) produce una mayor inclinación distal de los primeros y segundos molares en el tratamiento con arnés cervical.…”
Section: Resultados Y Discusiónunclassified
“…Algunos estudios reportan que el uso del arco extraoral es un dispositivo eficaz cuando se utiliza para la distalización de los primeros molares superiores para lograr una relación molar de clase I o para recuperar el espacio perdido por la pérdida prematura de piezas deciduas, no obstante, es común evidenciar que este movimiento distal es acompañado por una inclinación distal de la corona, por ello algunos autores recomiendan utilizar 300 gramos [40][41][42] .…”
Section: Reporte Del Casounclassified